THE STUDENTS’ ERRORS IN USING DIRECT AND INDIRECT SPEECH IN PAST FORM: A CASE STUDY AT THE SECOND GRADE STUDENTS OF MA PALAPA NUSANTARA NW SELEBUNG IN THE SCHOOL YEAR 2016/2017 - ABDUL MAJID JUNAIDI (LPPM Universitas Gunung Rinjani, 2020)
This research is aimed to know students’ errors in using direct and indirect speech in past form, a descriptive study at the second grade students of MA Palapa Nusantara NW Selebung in the school year 2016/2017. The numbers of population were 32 students which consist of one class. The researcher used a cluster sampling which took whole students of the second grade students of MA Palapa Nusantara NW Selebung in the school year 2016/2017 as a sample that were 32. In collecting the data, the researcher used a written test in form of completion and questionnaire. A test consists of 25 items of direct speech that would be changed into indirect speech. After the data was gathered, the researcher used qualitative descriptive method in analyzing the data where the researcher described the data qualitatively. Based on the result of data analysis, students encountered some types of errors in using direct and indirect speech in past form such as: omission, addition, miss formation and miss ordering.Key word: Students’ Error, Direct and Indirect Speech, Past Form.Penelitian ini bertujuan untuk mengetahui tempat kesalahan siswa didalam menggunakan kalimat langsung dan tidak langsung dalam bentuk lampau. Penelitian ini merupakan penelitian deskriptif yang dilakukan di kelas XI MA Palapa Nusantara NW Selebung Tahun ajaran 2016 / 2017. Jumlah sampel dalam penelitian ini adalah 32 siswa dalam satu kelas. Peneliti menggunakan teknik klaster sampeling didalam menentukan sampel penelitian. Ketika mengumpulkan data, peneliti menggunakan tes dan kuesioner. Tes dalam penelitian ini terdiri dari 25 pertanyaan kalimat langsung yang dirubah ke kalimat tidak langsung. Setelah data terkumpul, peneliti menganalisa data dengan menggunakan teknik kualitatif diskriptif. Berdasarkan hasil analisis data ditemukan beberapa jenis kesalahan siswa dalam menggunakan kalimat langsung dan tidak langsung seperti : penghilangan, penambahan, kesalahan bentuk dan kesalahan susunan.Kata Kunci : Kesalahan Siswa, Kalimat Langsung dan Tidak Langsung, Waktu Lampau.